HUBUNGAN PENGETAHUAN PERSONAL HYGIENE DENGAN GEJALA PENYAKIT KULIT PADA PEMULUNG DI TEMPAT PEMBUANGAN AKHIR SAMPAH SUWUNG DENPASAR TAHUN 2018 - I Komang Juli Angriyasa; made bulda; Moch Choirul Hadi (Poltekkes Kemenkes Denpasar, 2019)
The level of an individual’s education has a big contribution towards the mindset and health problems. The knowledge regarding personal hygiene is necessary to improve the health and behaviour of the ragpickers at Suwung landfill in preventing the symptoms of skin diseases. The purpose of this study was to determine the relationship of personal hygiene knowledge with the skin disease symptoms on ragpickers.This research was an analytical survey conducted through interview method with cross-sectional approach. The sample size was 70 ragpickers at Suwung landfill. The result of ragpickers’ knowledge at Suwung landfill was 15,7% of good, 45,7% of medium, and 38,6% of bad. The research found 54.3% samples had skin disease symptoms while 45.7% were negative. It was found that symptoms of skin diseases experienced such as itching, bumps, skin redness and scaly skin. From Chi-Square test results obtained p-value = 0.029 ɑ (0.05), means the knowledge of personal hygiene and the skin disease symptoms on the ragpickers had a significant relationship, with a weak level of relationship (CC value= 0,304). The conclusion, there was a relationship between personal hygiene knowledge and skin disease symptoms on ragpickers at the Suwung Landfill.